2004
DOI: 10.1002/lsm.20024
|View full text |Cite
|
Sign up to set email alerts
|

In vivo targeted gene transfer in skin by the use of laser‐induced stress waves

Abstract: Highly efficient and site-specific gene transfer can be achieved by applying a few pulses of nanosecond pulsed LISWs to rat skin in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 43 publications
2
71
1
Order By: Relevance
“…This makes such techniques particularly suitable for the transport of relatively hydrophilic macromolecules, including proteins. Examples of enhanced delivery of macromolecules with these technologies include human growth hormone (radiofrequencies) [89]; gene transfer (lasers) [90]; insulin by pulsed laser [91], sonophoresis [92] or electroporation [93]; vaccines by sonophoresis [94] or electroporation [95]. Disadvantages of cavitational techniques include the possibility of infection due to open pores and pain (particularly with electroporation).…”
Section: Cavitational Technologiesmentioning
confidence: 99%
“…This makes such techniques particularly suitable for the transport of relatively hydrophilic macromolecules, including proteins. Examples of enhanced delivery of macromolecules with these technologies include human growth hormone (radiofrequencies) [89]; gene transfer (lasers) [90]; insulin by pulsed laser [91], sonophoresis [92] or electroporation [93]; vaccines by sonophoresis [94] or electroporation [95]. Disadvantages of cavitational techniques include the possibility of infection due to open pores and pain (particularly with electroporation).…”
Section: Cavitational Technologiesmentioning
confidence: 99%
“…14 the gene transfer of a plasmid DNA and the expression level for laser-treated rat skin were two orders higher than the controlled skin; 15 the delivery of gene-coded plasmid into skin grafts was increased and the grafts adhesion was accelerated. 16 Besides, after QS-Nd:YAG laser (532 and 1064 nm) irradiation, both the concentration and penetration depth of methylene blue into biofilms were enhanced; 17 the penetration of 5-fluorouracil into irradiated rabbit ear skin was increased.…”
Section: Introductionmentioning
confidence: 99%
“…Mulholland et al have reported the laser-induced stress wave of a polyimide target, as a direct geometry, interacted with an ArF excimer laser (wavelength 193 nm, full width at half maximum: FWHM 29 ns, energy 350 mJ) [5]. Ogura et al have reported the laser-induced stress wave of a natural rubber target with a Polyethylene terephthalate (PET), as a confined geometry, interacted with a Nd:YAG pulse laser (wavelength 532 nm, FWHM 7.0 ns, laser fluence 1.9 J/cm 2 ) [6]. However, the observed waves in the two geometries have different characteristics in the generation process.…”
Section: Introductionmentioning
confidence: 99%